Hierarchical Neighborhood Models for Ventilation System - Shmyrin, A.M; Mishachev, N.M; Semina, V.V (International Journal of Engineering and Technology, 2018)
Considering cement production, we deal with dust, associated with a non-optimal operation of the dust-free ventilation system in the clinker burning department. The optimally organized heating, ventilating, and air conditioning system in any type of production ensures the microclimate of the production premises, corresponding to the sanitary norms and rules, which contribute to the increase of the staffâ€™s efficiency. In this paper, the questions of the neighborhood modeling of the heating, ventilating, and air conditioning system in the premises of the cement production shop are considered. A system for minimizing energy costs and reducing dust emission in the clinker burning shop is proposed, which allows increasing the environmental safety of production.Â
Keywords: .